Analysis of the Variation of Friction Coefficient of Sandstone Joint in Sliding. (29th October 2020) - Zhao, Guochao; Wang, Laigui; Zhao, Na; Yang, Jianlin; Li, Xilin
Abstract : The friction coefficient of rock joints is closely related to the stability of the slope. However, it is difficult to predict the friction coefficient due to the influence of surface roughness and mechanical properties of rocks. In this study, we use a method that combines theoretical analysis with a sandstone sliding friction test and propose a model to predict the friction coefficient of Sandstone Joint. A sandstone sliding friction test was performed on a self-made reciprocating sliding friction test device. Good agreement between the estimated values and test values verified the validity of the friction coefficient prediction model. Through an analysis of the friction coefficient in sandstone sliding, it was established that the larger the wear mass, the larger the friction coefficient in sliding, and the larger the wear area, the smaller the friction coefficient. With the cycles increasing of sandstone, the friction coefficient gradually decreased before finally reaching a stable value. Comparisons between the estimated value and test results showed that when the wear difference coefficient c  = 2.0 and the meshing friction amplification coefficient K  = 1.4, the minimum error was 2.89%. The results obtained are significant in the control of slope sliding.